Stability of Hematological Parameters in Woodland Caribou (Rangifer tarandus caribou) Blood Stored at 4°C - Piat, G.; Semalulu, S.; Florence, Z.; Nolan, J. (Rangifer, 1996)
Eighteen free-ranging female woodland caribou were captured in northern Alberta in January and February 1993. Blood was collected into ethylenediaminetetraacetate (EDTA) tubes which were packaged in coolers containing ice packs, and transported to the laboratory where they arrived within 48 hrs of collection. Complete blood counts (CBC) were performed on five consecutive days to assess the stability of hematological parameters. Average values of hematocrit (HCT), mean cell hemoglobin (MCH), mean cell volume (MCV), red cell distribution width (P-J3W), white blood cell count (WBC), and red blood cell count (RJ3C) remained stable with no statistically significant changes occurring during 5 days of post-collection storage at 4°C. Mean PvBC values exhibited significant differences (p<0.05) between geographic locations. Mean platelet volume (MPV) increased significantly (p<0.001) with storage time, while platelet (PLT) values decreased (p<0.001) over time and were significantly different (p<0.01) between locations. For optimal hematological results, it is recommended that sample analysis be performed within 24 hours of blood collection; however, if caribou blood samples are properly stored at 4°C, useful information may be obtained from stable parameters up to 5 days following collection.